Strict Liability and Product Safety: The Case of Dangerous Syrup in Indonesia in the Maqashid Syariah Perspective - HL, Rahmatiah; Arbani, Tri Suhendra; Risnah, Risnah; Akbar, Rahmatul (Universitas Islam Negeri Jakarta, 2023)
This study examined the issue of cough syrup linked to several deaths of children in Indonesia from the perspectives of Maqasid Sharia and Strict Liability Theory. This library research analyzed the problem through document studies, news reports, and official statements from related parties. The findings revealed a need for considering strict liability and maqashid al shariah principles to protect consumers Moreover, this research recommended the need for advanced deliberation and collaboration among stakeholders, ulama, and representative figures in the pharmaceutical industry to overcome this problem. Penelitian ini mengkaji kasus sirup obat batuk yang dikaitkan dengan beberapa kematian anak di Indonesia dalam perspektif Maqasid Sharia dan Strict Liability Theory. Penelitian kepustakaan ini menganalisis permasalahan melalui studi dokumen, pemberitaan, dan pernyataan resmi dari pihak terkait. Temuan dalam Penelitian ini mengungkapkan perlunya mempertimbangkan prinsip liabilitas dan maqashid al syariah yang ketat untuk melindungi konsumen. Selain itu, penelitian ini merekomendasikan perlunya musyawarah dan kolaborasi lanjutan antar pemangku kepentingan, ulama, dan tokoh perwakilan di industri farmasi untuk mengatasi masalah ini.